Reconceptualizing the Context-Design Issue for the Information Systems Function - Brown, Carol V.; Magill, Sharon L. (Organization Science, 1998)
The authors develop theory for predicting the distribution of decision making between the corporate and business-unit levels of management for a subset of information systems (IS) resources referred to as systems development. Drawing on literature from the fields of MIS, strategic management, and organization theory, they first determine how potentially influential context factors are likely to affect the locus of the lead decision-making role from a multiple-contingencies perspective. Then they theorize how conflicting corporate and business-unit contingencies are likely to be resolved. They present a set of six propositions that predict a centralized, decentralized, or compromise design solution for a given business unit on the basis of (1) business-level strategy, (2) whether or not information technology (IT) plays a strategic role for the business unit, (3) the degree of line managers' IT knowledge at the business-unit level, and (4) the level at which opportunities for IT-related synergies across business units are being pursued at the corporate level.